Angular Momentum Collinearization of an Elastic Gyro with Hysteresis - Rimrott, F. P. J.; Salustri, F. A. (Technische Mechanik - European Journal of Engineering Mechanics, 2019)
In the present paper it is shown in some detail how the energy dissipation in a deforming elastic gyro leads to a collinearization of the angular momenta, according to the collinearity principle.